(3TQM Ydi TGajI GHf GdMGLHs - (3eLghds ((3eMehO Hf GdMGL MSjf GdeQeGOgs)
(3ChdgG (B:s
... (3fMh GSJcJHg Cj WdHJ efg GdcJGHI hbO Jchf JbOjQG fMh (B...(3ef GdMGFW adjS efgG WdH UQjM Hd GdeYjf de CRd CJdWa hGdNjd MJi NQL hfqRd Pdc efRdI GdWdH (B... (3PcQ GdeUfa Cf eRjO GdKdGKj NeSI hYTQhf (B...s
(3BNQgG (B:s
... (3hCeG GdMQha ade jcJH TjA efgG HGdjGA Edj Hdi hEdi hYdi hMJi hCeG cfGHI Edi hYdi HGdjGA adbdH CdajgeG jGkA cY GdVejQ fMh Edjc hYdjc hCeG cfGHI MJi HGdjGA adMedgG Ydi Edi dchfgG HeYfGgG (B...(3hGSJZdGd GdEeGdI aj GdLdGddI Ydi GdjGA ZGdHG (B. (3hGddg CYdes
(3JHUQI GdeDda (B:s
(3fbd Yfg TeS GdOjf CMeO GdeYQha HOjcfbhR Ch OfbhR (B((3GdeJhai(B: 855(3g`(B) (3aj cJGHg TQMGf Ydi eQGM GdCQhGM aj Yde GdUQas
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdUQas